2006
DOI: 10.1002/jcb.20755
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis of apoptosis induced by sodium selenite in human acute promyelocytic leukemia NB4 cells

Abstract: Selenium (Se) is an essential trace element possessing anticarcinogenic properties. Sodium selenite (Na2SeO3) induced apoptosis in human acute promyelocytic leukemia (APL) cell line NB4 with dose and time dependency. In this study, proteomic techniques were used to study the apoptosis of NB4 cells induced by sodium selenite. Twenty-six downregulated and four upregulated proteins were identified, which exhibited a 1.5-fold change or greater. The identified proteins included key regulators of signal transduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Comparative 2D gel electrophoresis of sodium selenite-induced apoptosis in human leukemia NB4 cells has been performed and confirmed by RT-PCR and Western blot (Dong et al 2006). Out of the 26 downregulated and four upregulated proteins that exhibited a minimum 1.5 fold change in that study, only a-tubulin, b-actin and LAMR1 were also identified in our CHO IgG-9b8 study.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Comparative 2D gel electrophoresis of sodium selenite-induced apoptosis in human leukemia NB4 cells has been performed and confirmed by RT-PCR and Western blot (Dong et al 2006). Out of the 26 downregulated and four upregulated proteins that exhibited a minimum 1.5 fold change in that study, only a-tubulin, b-actin and LAMR1 were also identified in our CHO IgG-9b8 study.…”
Section: Discussionmentioning
confidence: 55%
“…Induced apoptosis has been studied in various cell lines using a number of approaches (Baik and Lee 2010;Dong et al 2006;Schmidt et al 2007;Thiede et al 2006). Comparative 2D gel electrophoresis of sodium selenite-induced apoptosis in human leukemia NB4 cells has been performed and confirmed by RT-PCR and Western blot (Dong et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The specific activation of p38 and JNK in cells exposed to various selenium compounds has been reported by several authors (Ghose et al 2001;Jiang et al 2004a, b;Kim et al 2004;Dong et al 2006). On the other hand, ebselen and selenite have been shown to inhibit p38 and JNK pathways by thiol-redox mechanism (Park et al 2000;Sarker et al 2003).…”
Section: Discussionmentioning
confidence: 82%
“…In acute promyelocytic leukemia (APL) this compound induced apoptosis [180]. The kinases that are modulated by sodium selenite include the MAPK family, serine threonine kinase receptor-associated protein (UNRIP), c-Myc, c-Jun and cFos.…”
Section: Methylseleninic Acid and Sodium Selenitementioning
confidence: 99%